Follow-up with Diffusion-Weighted Imaging After Nonsurgical Radiotherapy for Early Breast Cancer (Department of Radiology, Medical Faculty, University of Brawijaya, 2025)
Nonsurgical radiotherapy is a new treatment option for patients with early-stage, operable breast cancer. However, there is no standard imaging method for follow-up after radiotherapy. A 61-year-old woman with early-stage operable right breast cancer was treated with radical radiotherapy using helical tomotherapy. After delivering 50 Gy in 25 fractions to the whole breast, adaptive boost radiotherapy was delivered to the residual tumor with a total dose of 30 Gy in 10 fractions. A 61-year-old woman with early-stage operable right breast cancer underwent radical radiotherapy with helical tomotherapy. After delivering 50 Gy in 25 fractions to the whole breast, adaptive boost radiotherapy was delivered to the residual tumor with a total dose of 30 Gy in 10 fractions. There were no serious adverse events during radiotherapy and 6 years of follow-up. After radiotherapy, non-contrast MRI with diffusion-weighted imaging was performed every 6 months. The tumor completely disappeared 24 months after radiotherapy,The tumor completely disappeared 24 months after radiotherapy, and recurrence was not evident during 6 years of follow-up. In conclusion, upfront adaptive radiotherapy with helical tomotherapy may be a viable option for patients with early breast cancer,, and non-contrast MRI with diffusion-weighted imaging may be a valuable imaging modality for follow-up.